THE CORRELATIONS AMONG CONSTRUCTS IN THE HEALTH BELIEF MODEL AND SELF-EFFICACY IN APPLYING THE NEWLY DEVELOPED INDONESIAN MODEL OF ASSERTIVE COMMUNICATION (CERDAS) - Puspitawati, Theresia; Prabandari, Yayi Suryo; Sastrowijoto, Soenarto; Paramastri, Ira; Claramita, Mora (YCAB Publisher & IAKMI SULTRA, 2018)
Background: One of the most important factors in providing health services is communication. Effective communication between patient-physician will have an impact on health outcomes. Nevertheless, a gap still occurs in patient-physician communication.Objective: This study aimed to determine the correlation between the core concepts of the well-established Health Belief Model: perceived susceptibility, perceived severity, perceived benefits, perceived barriers and cues to action with the concept of self-efficacy in applying the newly developed Indonesian Model of Assertive Communication called